Primary production at the Bransfield Strate during March 2002 - Chmyr, V. D.; Sysoyev, A. A. (Ukrainian Antarctic Journal, 2004)
Primary production (PP) rates were measured by a radiocarbon method at 28 stations in the southwestern Bransfield Strait (BS) during 9 – 21 March 2002. More productive waters with PP rates in excess of 10 mg C m-3 day-1 for surface layer were in the central and northern BS. Here and at one station in the Gerlach Strait the maximal PP rates in excess of 20 mg C m-3 day-1 were determined. Minimal PP values 2 -5 mg C m-3 day-1 we documented in the southern BS along the Antarctic Peninsula. The integrated primary production values for the euphotic zone by the measurings at 8 stations ranged from 75 to 244 mg C m-2 day-1. Mean PP rates were 8,9 mg C m-3 day-1 (1,92 – 24,51) for the surface layer and 144 mg C m-2 day-1 for the euphotic zone. The anomalous cold summer, strong storms and early winter coming in March 2002 may explain low PP rates in the productive BS area.